Ornamentation of dermal bones of Placodermi from the Lower Devonian of Morocco as a measure of biodiversity - Antczak, Mateusz; Berkowski, Błażej (Geologos, 2017)
Dermal bones are formed early during growth and thus constitute an important tool in studies of ontogenetic and evolutionary changes amongst early vertebrates. Ornamentation of dermal bones of terrestrial vertebrates is often used as a taxonomic tool, for instance in Aetosauria, extant lungfishes (Dipnoi) and ray-finned fishes (Actinopterygii), for which it have been proved to be of use in differentiating specimens to species level. However, it has not been utilised to the same extent in placoderms. Several features of the ornamentation of Early Devonian placoderms from Hamar Laghdad (Morocco) were examined using both optical and scanning electron microscopy to determine whether it is possible to distinguish armoured Palaeozoic fishes. Four distinct morphotypes, based on ornamentation of dermal bones, are differentiated. These distinct types of ornamentation may be the result of either different location of dermal plates on the body or of ontogenetic (intraspecific) and/or interspecific variation.